Assessment of cardiometabolic response during horse riding - Marongiu, E.; Sainas, G.; Corona, F.; Loi, A.; Tocco, F.; Concu, A.; Crisafulli, A. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Few studies have addressed the physiological demands of riding. Oxygen uptake has been demonstrated ranging between 40% and 80% of maximal aerobic capacity (VO2max) previously assessed, depending on different equine gaits. From these studies it can be inferred that the metabolic requirement of riding is similar to that of other physical activities, such as aerobics or gymnastics. The aim of the present study was to investigate on the cardiometabolic response in a group of riders during different gaits of equine movement. Methods: Ten riders were enrolled. They underwent two different tests: A) a standard incremental cardiopulmonary test (CPT) until exhaustion on an electromagnetically braked cycle ergometer. Oxygen uptake (VO2), carbon dioxide production (VCO2), pulmonary ventilation (Ve), and heart rate (HR) were measured by a gas analyzer (Ultima CPX, MedGraphics, USA). B) Riding session (RS), which consisted in 5 minutes of walking, 10 minutes of trot, and 10 minutes of cantering. Throughout RS, VO2, VCO2, Ve and HR were collected by a portable telemetric metabolimeter (VO2000, MedGraphics, USA). Excess of carbon dioxide production (CO2 excess) was also calculated as an index of anaerobic energy supply engagement. Parameters collected during RS were compared to values achieved during CPT. Moreover, parameters` levels during each gait were compared. Results: VO2, Ve, VCO2 and HR mean values gathered during RS were below the maximum reached during CPT. Furthermore, all these parameters were below the level achieved at the anaerobic threshold. VO2 raised significantly from 505.1±130.8 ml/min during walking 1133.9±230 ml/min during cantering (p<0.05). Cantering also increased HR with respect to walking (149.6± 24.7 bpm vs. 100±14.9 bpm respectively, p<0.05). Finally, statistics revealed significant increase in CO2 excess during cantering (200.4±98.1 ml/min) with respect to trotting (102.8±58.8 ml/min) and walking (48.7±34.5 ml/min) (p<0.05 in both cases). Conclusions: Data from the present investigation demonstrate that each of the different gaits of equine movement requires different metabolic response. It appears that, while walking and trotting involve predominantly the aerobic metabolism, during cantering the anaerobic metabolisms are recruited. This fact probably reflects the diverse pattern of riders` muscle contraction during each of the equine movements.